Mahasiswi Kesejahteraan Sosial FISIP USU Meningkatkan Rasa Percaya Diri Anak Melalui Pendekatan Sosial - Nasution, Khoirul Bariyyah; Pirandy, Gusty (Yayasan Daarul Huda Kruengmane, 2025)
The author conducted practicum 1 at the Ora Era Labora orphanage. The practicum conducted by the author was to research what was experienced by the orphanage children. The problems experienced by the orphanage children were lack of self-confidence,difficulty in social interaction with peers and adults, and obstacles in adapting to the surrounding environment. From these problems, the author was interested and had the goal of understanding more deeply the conditions of the orphanage childreen and designing interventions that could support increasing self-confidence, social interaction skills, and their ability to adapt in everyday life. The authors has individual clients who experience these problems, who are still in elementary school (SD). The author uses the case work stages in his research from the assesment stage to the termination stage. The method used is a qualitative approach with observasion techniques, interviews, and social assessment using ecomap tools.